2016
DOI: 10.1104/pp.15.01929
|View full text |Cite
|
Sign up to set email alerts
|

Programming of Plant Leaf Senescence with Temporal and Inter-Organellar Coordination of Transcriptome in Arabidopsis1  

Abstract: Plant leaves, harvesting light energy and fixing CO 2 , are a major source of foods on the earth. Leaves undergo developmental and physiological shifts during their lifespan, ending with senescence and death. We characterized the key regulatory features of the leaf transcriptome during aging by analyzing total-and small-RNA transcriptomes throughout the lifespan of Arabidopsis (Arabidopsis thaliana) leaves at multidimensions, including age, RNA-type, and organelle. Intriguingly, senescing leaves showed more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(159 citation statements)
references
References 86 publications
8
139
0
Order By: Relevance
“…To select proteases implicated in leaf senescence, we compared the transcript levels for Arabidopsis protease-encoding genes in green and senescent leaves from a recently published leaf development time course [54]. We binned these proteases into 41 protease families according to the MEROPS peptidase database [7].…”
Section: Resultsmentioning
confidence: 99%
“…To select proteases implicated in leaf senescence, we compared the transcript levels for Arabidopsis protease-encoding genes in green and senescent leaves from a recently published leaf development time course [54]. We binned these proteases into 41 protease families according to the MEROPS peptidase database [7].…”
Section: Resultsmentioning
confidence: 99%
“…f–j). Furthermore, similar to other senescence regulators like RELATED TO ABI3/VP1 or AUXIN RESPONSIVE FACTOR2 (Lim et al ., ; Woo et al ., , ), GVS1 transcript levels gradually increase with leaf age, reaching a maximum at the early senescence stage but decreasing as senescence proceeds (Fig. S8), indicating that GVS1 might be important in regulating the initiation of leaf senescence.…”
Section: Resultsmentioning
confidence: 92%
“…A total of 1197 (90.1%) of 1318 genes belonged to SAGs, further supporting the dedicated functions of GVS1 in the regulation of SAGs. Next we identified the biological processes enriched within 1318 genes compared to the 5836 SAG s. This analysis showed that GVS1 predominantly modulates a variety of essential biological processes previously identified to occur during leaf senescence (Breeze et al ., ; Woo et al ., ), such as organ senescence, defense responses, photosynthetic processes, metabolic processes and transport, and protein regulation (Fig. e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the comparison of different biological systems, we selected the significantly enriched gene ontologies from our N. benthamiana RNAseq experiment (p and q values <0.05) and compared their Z-score values with those obtained from the analysis of published RNAseq data of tomato fruit ripening and Arabidopsis leaf senescence. In particular, we used the RPM values of the total pericarp at mature green (MG), light ripe (LR) and red ripe (RR) stages (Shinozaki et al, 2018) and the FPKM values of the 16D and 30D senescence stages (Woo et al, 2016). DEGs resulting from LR/MG, RR/MG and 30D/16D comparisons were filtered as described above for N. benthamiana crtB/GFP.Student's t-tests were used for the rest of statistical analyses using GraphPad Prism 5.0a (GraphPad Software).…”
Section: Statistical Analysesmentioning
confidence: 99%